2016
DOI: 10.3109/00365513.2015.1137350
|View full text |Cite
|
Sign up to set email alerts
|

Effects of short-term mechanical hyperventilation on cerebral blood flow and dynamic cerebral autoregulation in critically ill patients with sepsis

Abstract: In sepsis, higher PaCO2 levels are associated with impaired dynamic cerebral autoregulation (dCA), which may expose the brain to hypo- and hyperperfusion during acute fluctuations in blood pressure. We hypothesised that short-term mechanical hyperventilation would dCA in critically ill patients with sepsis. Seven mechanically ventilated septic patients were included. We assessed dCA before and after 30 min of mechanical hyperventilation. Transfer function analysis of spontaneous oscillations in transcranial Do… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(20 citation statements)
references
References 51 publications
(109 reference statements)
0
14
1
Order By: Relevance
“…The remaining 74 articles underwent full article review and of these studies, and 24 studies were included in the final analysis—15 pre‐clinical (Table ) 7,8,20‐32 and nine clinical (Table 1). 5,12,33‐39 The pre‐clinical studies included 547 animals and the clinical studies included 5022 subjects. Study quality for each study is described in Tables S2 and S3.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The remaining 74 articles underwent full article review and of these studies, and 24 studies were included in the final analysis—15 pre‐clinical (Table ) 7,8,20‐32 and nine clinical (Table 1). 5,12,33‐39 The pre‐clinical studies included 547 animals and the clinical studies included 5022 subjects. Study quality for each study is described in Tables S2 and S3.…”
Section: Resultsmentioning
confidence: 99%
“…PaCO 2 , partial pressure of carbondioxide nine clinical (Table 1). 5,12,[33][34][35][36][37][38][39] The pre-clinical studies included 547 animals and the clinical studies included 5022 subjects. Study quality for each study is described in Tables S2 and S3.…”
Section: Search and Selectionmentioning
confidence: 99%
See 1 more Smart Citation
“…109,110,113,114 Several studies have evaluated cerebrovascular reactivity in sepsis, generally finding it to be normal or increased. 40,106,111,[115][116][117] Vaskó et al 115 reported increased rScO 2 after the administration of acetazolamide suggesting preserved cerebrovascular reactivity in patients with severe sepsis but point out that this could be artefactual. The increased rScO 2 was likely due to selective arteriolar vasodilation from acetazolamide which NIRS algorithms misinterpret as increased CBF given their assumption of a fixed arterial:venous ratio.…”
Section: Cbf Autoregulation In Sepsismentioning
confidence: 99%
“…Indeed, monitoring CA has shown to be particularly useful in the context of acute subarachnoid hemorrhage, traumatic brain injury (TBI), and acute stroke (2)(3)(4)(5). Although no randomized controlled trials (RCTs) assessing the effect of autoregulation on outcome are available at present, it is accepted among experts that impairment of CA can lead to secondary cerebral insult and poor outcomes also in patients without primary brain injury (6)(7)(8)(9)(10).…”
Section: Introductionmentioning
confidence: 99%